Entre a televisão e as artes visuais : a "estética da aproximação" em produções seriadas de Luiz Fernando Carvalho (2005 a 2010) - Castro, Isabel Alencar de (2017)
The current thesis lays between television and visual arts and it has as its study object the series production of the director Luiz Fernando Carvalho, through chosen scenes of the miniseries “Hoje é dia de Maria” (2005) and of the microseries “Capitu” (2008) and “Afinal, o que querem as mulheres?” (2010). The objectives of the thesis are to investigate the relations between moving pictures and the visual arts which emerge in the aesthetic of the series produced by the director, contextualize Carvalhos’s work in the national production of short series, as well as his path as a director; stablish symmetric visual relations between television images and the chosen paintings; characterize and differentiate Carvalho’s aesthetics in the selected series; and comprehend how the selected miniseries renewed the televisual aesthetics field. The main authours studied were Figueiredo (2003); Mattos (2010); Ribeiro and Sacramento (2010); Esquenazi (2011), Pallottini (2012); Bazin (2014); Badiou (2014); Lebrun (1988). The inquiry began from the concept of “impurity”, from Badiou (2002), which was added to the concepts of “presence/absence” and “Stimmung”, from Gumbrecht (2014), thus to outline the proposal of the “Proximity Aesthetics”. The proposal was constructed from the intertwining of the audiovisual scenes and the related paintings associated to them, in which it was possible to infer a common constructive action, named “symmetry of the artistic procedure”.